Juvenile Angiofibroma - Dubey, Siba P.; Schick, Bernhard (Springer International Publishing : Imprint: Springer, 2017)
This book provides a comprehensive up-to-date review of juvenile angiofibroma, with contributions from all relevant specialties. Starting with a brief introduction to the history, etiology and relevant anatomy, the book goes on to discuss the pathology, clinical features and treatment of this disease in depth, concluding with a summary of current controversies. Juvenile Angiofibroma is aimed at a global audience of otolaryngologists, endoscopists, head and neck surgeons, maxillofacial surgeons, pathologists, radiologists and geneticists.